2012
DOI: 10.1177/0098628312437721
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Successful Undergraduate Psychology Programs

Abstract: Scholarly writings provide guidance for delivery of an undergraduate program in psychology (e.g., APA, 2007;Halpern, 2010). Much of the emphasis in this literature has been on examination of the curriculum (e.g., McGovern, 1993;Stoloff et al., 2010), yet minimal research has been conducted to empirically link the overall undergraduate psychology major experience with outcomes. This article relates program characteristics (including curriculum, resources, and faculty engagement) to student success and satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 14 publications
(30 reference statements)
2
40
1
Order By: Relevance
“…In Stoloff et al (2012), we demonstrated that the combination of experiential learning, certain institutional characteristics, and student-faculty interaction explained 28.4% of the variance in graduate school attendance. We also found that student experiences matter; that is, frequent experiential learning and student-faculty interaction predicted graduate school attendance, after controlling for institutional characteristics.…”
Section: Relating Student Experiences To Measures Of Student Successmentioning
confidence: 91%
See 1 more Smart Citation
“…In Stoloff et al (2012), we demonstrated that the combination of experiential learning, certain institutional characteristics, and student-faculty interaction explained 28.4% of the variance in graduate school attendance. We also found that student experiences matter; that is, frequent experiential learning and student-faculty interaction predicted graduate school attendance, after controlling for institutional characteristics.…”
Section: Relating Student Experiences To Measures Of Student Successmentioning
confidence: 91%
“…We related the frequency of these experiences to measures of student success used by Stoloff et al (2012), including (a) the percentage of students entering graduate school, (b) overall program standardized MFT or ACAT test scores, and (c) program completion rate.…”
Section: Relating Student Experiences To Measures Of Student Successmentioning
confidence: 99%
“…Other studies have explored experiential learning in different contexts and with different sample groups, including students studying abroad (Intolubbe-Chmil, Spreen and Swap 2012), research participation (Bowman and Waite, 2003), and increasing cultural competency (Earnest, Rosenbusch, Wallace-Williams and Keim 2016). Frequency of experiential learning has also been found to be an important factor for student success in psychology (Stoloff, Curtis, Rodgers, Brewster and McCarthy 2012).…”
Section: Experiential Learningmentioning
confidence: 99%
“…The My Virtual Child© programme includes features of good teaching practices as previously proposed by various research studies, such as experiential learning opportunities (Stoloff et al, 2012), interactive activities (Wilson, 2013), social networking and interactive sites (Blessing et al, 2012;Stansbury & Munro, 2013;Twenge, 2013).…”
Section: Concluding Remarks: Implications For Practicementioning
confidence: 99%